HMGB1 mediates lipopolysaccharide-induced macrophage autophagy and pyroptosis - Jiawei Shang; Feng Zhao; Yongmei Cao; Feng Ping; Wei Wang; Yingchuan Li (BMC Molecular and Cell Biology, 2023)
Abstract Autophagy and pyroptosis of macrophages play important protective or detrimental roles in sepsis. However, the underlying mechanisms remain unclear. High mobility group box protein 1 (HMGB1) is associated with both pyroptosis and autophagy. lipopolysaccharide (LPS) is an important pathogenic factor involved in sepsis. Lentivirus-mediated HMGB1 shRNA was used to inhibit the expression of HMGB1. Macrophages were treated with acetylation inhibitor (AA) to suppress the translocation of HMGB1 from the nucleus to the cytosol. Autophagy and pyroptosis-related protein expressions were detected by Western blot. The levels of caspase-1 activity were detected and the rate of pyroptotic cells was detected by flow cytometry. LPS induced autophagy and pyroptosis of macrophages at different stages, and HMGB1 downregulation decreased LPS-induced autophagy and pyroptosis. Treatment with acetylation inhibitor (anacardic acid) significantly suppressed LPS-induced autophagy, an effect that was not reversed by exogenous HMGB1, suggesting that cytoplasmic HMGB1 mediates LPS-induced autophagy of macrophages. Anacardic acid or an anti-HMGB1 antibody inhibited LPS-induced pyroptosis of macrophages. HMGB1 alone induced pyroptosis of macrophages and this effect was inhibited by anti-HMGB1 antibody, suggesting that extracellular HMGB1 induces macrophage pyroptosis and mediates LPS-induced pyroptosis. In summary, HMGB1 plays different roles in mediating LPS-induced autophagy and triggering pyroptosis according to subcellular localization.